Analisis Retorika Pada Pidato Pertama Purbaya Yudhi Sadewa Sebagai Menteri Keuangan - Ardan Saputra; Arie Azhari Nasution; Dedy Rahmad Sitinjak (JIKA (Jurnal Ilmu Komunikasi Andalan), 2026)
A speech is one of the forms of public communication that serves to convey ideas, build self-image, and influence the audience through the power of language. The speeches of state officials, particularly those delivered during a handover ceremony, are interesting to study because they contain rhetorical values that reflect a leader’s character, credibility, and communication strategy. This study aims to analyze the rhetorical elements in Purbaya Yudhi Sadewa’s first speech as Minister of Finance, delivered through the CNN Indonesia YouTube channel on September 8, 2025. The research employs a descriptive qualitative approach using Aristotle’s rhetorical framework (Ethos, Pathos, Logos) and Cicero’s five classical rhetorical principles (Inventio, Disposito, Elocutio, Actio, Memoria). The findings reveal that Ethos is the dominant element in the speech, as Purbaya emphasizes credibility, moral responsibility, and integrity as a newly appointed public official. Meanwhile, among Cicero’s five principles, Actio (delivery) is the most prominent aspect, characterized by effective expressions, gestures, and eye contact, whereas Memoria (memory) is the least evident due to reliance on the written text. The study concludes that Purbaya’s speech successfully reflects an ethical, authoritative, and persuasive communication style, strengthening his professional leadership image before the public. Based on these findings, it is suggested that future studies on rhetoric analyze the speeches of other public officials through a multimodal approach to achieve a more comprehensive understanding of rhetorical effectiveness in political and governmental communication.